2020
DOI: 10.1080/03014460.2020.1779815
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index, physical activity and motor competence in children: moderation analysis by different environmental contexts

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version mayremain and you are advised to consult the published version if you wish to cite from it. Title: Association between body mass index, physical activity and motor competence in children: Moderation analysis by different environmental contexts. Background: Although the association between body mass index (BMI), physical activity (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…However, results of this study also yielded a slightly negative regression path of extrinsic motivation on physical performance, indicating that extrinsic motivation is rather detrimental for children's physical performance. In addition, girls and children with a higher BMI had a significantly lower physical self-concept and a lower total performance score than boys and children with a lower BMI, as also earlier shown in previous studies (e.g., Deaner et al, 2016;Ferreira et al, 2019;Queiroz et al, 2020). By implication, girls and children with a higher BMI are at risk and should be supported in physical activities by, for instance, specific physical tests related to their individual motor skills to sustainably motivate them to more physical activities and a healthier lifestyle.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, results of this study also yielded a slightly negative regression path of extrinsic motivation on physical performance, indicating that extrinsic motivation is rather detrimental for children's physical performance. In addition, girls and children with a higher BMI had a significantly lower physical self-concept and a lower total performance score than boys and children with a lower BMI, as also earlier shown in previous studies (e.g., Deaner et al, 2016;Ferreira et al, 2019;Queiroz et al, 2020). By implication, girls and children with a higher BMI are at risk and should be supported in physical activities by, for instance, specific physical tests related to their individual motor skills to sustainably motivate them to more physical activities and a healthier lifestyle.…”
Section: Discussionsupporting
confidence: 85%
“…Interventions targeted at improving younger children's physical performance should thus establish conditions to promote children's physical selfconcept and intrinsic motivation by means of adapting the level of motor skill tests to children's individual physical abilities, providing positive feedback to their physical performance, and enhancing their individual progress (Deci and Ryan, 2002). This may be of particular importance for girls and children with a higher BMI who showed a much lower physical self-concept and poorer physical performance in this study and many other studies (e.g., Morano et al, 2011;Zsakai et al, 2017;Ferreira et al, 2019;Queiroz et al, 2020).…”
Section: Implications and Conclusionmentioning
confidence: 56%
“…[ 68 , 69 , 70 ]. In addition, Barnett et al [ 71 ] suggested that variables such as age, gender, and weight status affect MC, while Queiroz et al [ 72 ] found a positive modulation and improvement of motor skills (in addition to body mass index (BMI)) in the youth who had higher access to PA thanks to improved environmental contexts, sports facilities, or sports clubs. The current results underline the relation between PA practice and central nervous system development [ 73 ], in this context, MC evaluation acts as an indirect healthy growth indicator [ 71 ].…”
Section: Motor Competence In Childrenmentioning
confidence: 99%
“… Barnett et al (2016) suggesting that variables such as age, sex and weight status affect GMC while Queiroz et al (2020) found a positive modulation and improvements of GCM (in addition to body mass index (BMI)) in young belonging to a family with a high socio-economic-status family that permit higher possibilities to access in environmental contexts, sports facilities or sports clubs. These results underline the connection between motor practice and central nervous system development ( Davids, Button & Bennett, 2008 ) where the evaluation of GMC is often used as an indirect measure of healthy development ( Barnett et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%